Polymer–lipid hybrid anti-HER2 nanoparticles for targeted salinomycin delivery to HER2-positive breast cancer stem cells and cancer cells - Li J (Dove Medical Press, 2017)
Jun Li,1,* Wenqing Xu,2,* Xiaoli Yuan,3,* Huaiwen Chen,3 Hao Song,1,4 Bingquan Wang,5 Jun Han5 1College of Pharmacy, Liaocheng University, Liaocheng, Shandong, 2Railway Police College, Zhengzhou, 3Department of Cadre Health Care, Nanjing General Hospital of Nanjing Military Command, Nanjing, Jiangsu, 4Centre for Stem Cell & Regenerative Medicine, Liaocheng People’s Hospital, 5Institute of Biopharmaceutical Research, Liaocheng University, Liaocheng, Shandong, China *These authors contributed equally to this work Purpose: Breast cancer stem cells (CSCs) are responsible for the initiation, recurrence, and metastasis of breast cancer. Sufficient evidence has established that breast cancer cells can spontaneously turn into breast CSCs. Thus, it is essential to simultaneously target breast CSCs and cancer cells to maximize the efficacy of breast cancer therapy. HER2 has been found to be overexpressed in both breast CSCs and cancer cells. We developed salinomycin-loaded polymer–lipid hybrid anti-HER2 nanoparticles (Sali-NP-HER2) to target both HER2-positive breast CSCs and cancer cells.Methods: The antitumor activity of Sali-NP-HER2 constructed by conjugating anti-HER2 antibodies to polymer–lipid salinomycin nanoparticles was evaluated in vitro and in vivo.Results: Sali-NP-HER2 efficiently bound to HER2-positive breast CSCs and cancer cells, resulting in enhanced cytotoxic effects compared with non-targeted nanoparticles or salinomycin. In mice bearing breast cancer xenografts, administration of Sali-NP-HER2 exhibited superior efficacy in inhibiting tumor growth. Sali-NP-HER2 reduced the breast tumorsphere formation rate and the proportion of breast CSCs more effectively than non-targeted nanoparticles or salinomycin alone.Conclusion: Sali-NP-HER2 represents a promising approach in treating HER2-positive breast cancer by targeting both breast CSCs and cancer cells. Keywords: nanoparticles, breast cancer, cancer stem cells, salinomycin, HER2